Pengaruh Harga dan Promosi Digital terhadap Loyalitas dengan Kualitas Layanan Sebagai Mediasi pada Pengguna Internet IDEOO di Kabupaten Bogor - Dwi Cahyoko; Musa Alkadhim Alhabsy; Rudiyanto Rudiyanto (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2026)
This study examines the effects of price and digital promotion on customer loyalty, with service quality as a mediating variable, among IDEOO internet users in Bogor Regency. A quantitative research design was employed using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) approach. Data were collected from 216 respondents selected through purposive sampling via a structured questionnaire measuring price, digital promotion, service quality, and customer loyalty. The results indicate that price has a positive and significant effect on service quality (β = 0.703), while digital promotion shows a weaker but significant effect on service quality (β = 0.247). Service quality has a strong and significant direct effect on customer loyalty (β = 0.663). Price demonstrates a significant indirect effect on loyalty through service quality (β = 0.466), whereas its direct effect on loyalty is insignificant (β = 0.213). Similarly, digital promotion has an insignificant direct effect on loyalty (β = 0.091) but exhibits a significant indirect effect through service quality (β = 0.164). These findings confirm the critical mediating role of service quality in strengthening customer loyalty to IDEOO internet services. Although price and digital promotion contribute positively, service quality emerges as the most influential determinant of loyalty. The study suggests that the strategic integration of competitive pricing, effective digital promotion, and superior service quality is essential for enhancing customer loyalty, competitiveness, and long-term trust in the broadband service industry.